Reducing branched-chain amino acids improves cardiac stress response in mice by decreasing histone H3K23 propionylation - Yang, Zhi; He, Minzhen; Austin, Julianne; Sayed, Danish; Abdellatif, Maha (The Journal of Clinical Investigation, 2023)
Identification of branched-chain amino acid (BCAA) oxidation enzymes in the nucleus led us to predict that they are a source of the propionyl-CoA that is utilized for histone propionylation and, thereby, regulate gene expression. To investigate the effects of BCAAs on the development of cardiac hypertrophy and failure, we applied pressure overload on the heart in mice maintained on a diet with standard levels of BCAAs (BCAA control) versus a BCAA-free diet. The former was associated with an increase in histone H3K23-propionyl (H3K23Pr) at the promoters of upregulated genes (e.g., cell signaling and extracellular matrix genes) and a decrease at the promoters of downregulated genes (e.g., electron transfer complex [ETC I–V] and metabolic genes). Intriguingly, the BCAA-free diet tempered the increases in promoter H3K23Pr, thus reducing collagen gene expression and fibrosis during cardiac hypertrophy. Conversely, the BCAA-free diet inhibited the reductions in promoter H3K23Pr and abolished the downregulation of ETC I–V subunits, enhanced mitochondrial respiration, and curbed the progression of cardiac hypertrophy. Thus, lowering the intake of BCAAs reduced pressure overload–induced changes in histone propionylation–dependent gene expression in the heart, which retarded the development of cardiomyopathy.